Perspectives on Translating YHWH in Papua New Guinea - King, Phil (The Bible translator, 2014)
Translating the word YHWH, the name of God in the Hebrew Bible, is a complex matter involving theological, linguistic, and cultural issues. This article considers six possible broad translation options for this name, and summarises case studies of thirty-one Papua New Guinean Old Testament translation projects, exploring and classifying the choices they have made and the issues that guided those choices. It ends by offering some of the advantages and disadvantages of the different possible translation options, as an aid to other translators working on Old Testament translation.